Analisis Modal Kerja terhadap Profitabilitas dan Aktivitas pada PT. Astra Agro Lestari Tbk. 2017-2021 - Puji Wahyuli; Nurfitri Martaliah; Siti Nur Khoiria; Rifadli D. Kadir (Study Program Ekonomi Syari'ah, Sekolah Tinggi Agama Islam Muhammadiyah Tulungagung, 2022)
PT Astra Agro Lestari Tbk. is a company engaged in the plantation industry in Indonesia and the company has also been included in the list of companies listed on the IDX (Indonesian Stock Exchange). The purpose of this study is to understand how the working capital conditions and profitability of PT. Astra Agro Lestari Tbk and how the influence between the two. This study uses the time series method for regression model analysis by determining the dependent and independent variables. The subjects obtained in this study came from the official website of the IDX (Indonesian Stock Exchange) for the period 2017-2021. In using the time series method and Classical Assumption Test to process the financial data of PT. Astra Agro Lestari Tbk. through the SPSS program. The results of this study indicate the amount of working capital at PT Astra Agro Lestari Tbk and how the profitability ratios use ROE and ROA at the company. Based on the results, it is found that the coefficient of determination is 0.486 which indicates that there is an influence of working capital on the profitability of PT Astra Agro Lestari.